Evaluating three calibration transfer methods for predictions of soil properties using mid‐infrared spectroscopy. Issue 3 (6th April 2021) - Pittaki‐Chrysodonta, Zampela; Hartemink, Alfred E.; Sanderman, Jonathan; Ge, Yufeng; Huang, Jingyi
Abstract: Mid‐infrared (MIR) spectroscopy models have been developed for rapid assessment of soils but are often soil and instrument specific because of differences in laboratory conditions and sensor setup. Calibration transfer is required to apply a spectral model such as partial least squares (PLS) regression developed from a primary instrument to a spectral dataset measured by a secondary instrument with statistically retained accuracy and precision. The study aimed to compare the performance of three transfer methods (i.e., direct standardization [DS], piecewise direct standardization [PDS], and spectral space transfer [SST]) and investigate the effects of transfer sample size and sample selection methods. The transfer methods were developed for predicting total C, clay, silt, and sand contents, cation exchange capacity (CEC), pH in water (pHW ) and CaCl2, CaCO3 equivalent, and −1, 500‐kPa water retention using spectral measurements of a secondary instrument. Calibration transfer methods of three PLS models for estimating soil properties with a high (total C), intermediate (clay content), and low (pHW ) predictability were discussed. The effect of sample size required for the development of the calibration transfer and the selection method of the transferred samples were investigated. It was found that SST was most favorable for a relatively small sample size used in calibration transfer (≤12 samples). The performance of transfer methods was optimal when the transfer samples accounted for the variability of MIR spectra from the secondary instrument. We conclude that SST and PDS have the potential to be applied in spectroscopy for predicting soil properties using secondary instruments. Core Ideas: Piecewise direct standardization (PDS) and spectral space transformation (SST) perform best. The SST was most favorable for a relatively small number of transfer samples. The performance of the SST was not influenced by the variability of the soil property.